2006
DOI: 10.1083/jcb.200607008
|View full text |Cite
|
Sign up to set email alerts
|

Spatial codes in dendritic BC1 RNA

Abstract: BC1 RNA is a dendritic untranslated RNA that has been implicated in local translational control mechanisms in neurons. Prerequisite for a functional role of the RNA in synaptodendritic domains is its targeted delivery along the dendritic extent. We report here that the targeting-competent 5′ BC1 domain carries two dendritic targeting codes. One code, specifying somatic export, is located in the medial-basal region of the 5′ BC1 stem-loop structure. It is defined by an export-determinant stem-bulge motif. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
185
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(188 citation statements)
references
References 64 publications
2
185
1
Order By: Relevance
“…PKM RNA also contains an A2RE-like dendritic-tar- geting element (Muslimov et al, 2006) that binds to hnRNP A2, suggesting that it follows the same A2 pathway. Thus, the A2 pathway may be a general pathway for multiplexed dendritic targeting of several different A2RE RNAs in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PKM RNA also contains an A2RE-like dendritic-tar- geting element (Muslimov et al, 2006) that binds to hnRNP A2, suggesting that it follows the same A2 pathway. Thus, the A2 pathway may be a general pathway for multiplexed dendritic targeting of several different A2RE RNAs in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…FCCS binding isotherms for binding of hnRNP A2 to A2RE sequences from rat MBP, mouse ␣CaMKII, rat NG, rat ARC RNAs, and antisense are shown in Figure 4, High-affinity sequence-specific binding of A2RE sequences to hnRNP A2 may provide the basis for selectivity in distinguishing A2RE from non-A2RE RNAs in the A2 pathway. A putative A2RE-like sequence from BC1 RNA (Muslimov et al, 2006) did not bind with high-affinity to hnRNP A2 (data not shown), suggesting that this sequence does not mediate dendritic targeting of BC1 RNA by the A2 pathway. Because hnRNP A2 binds with high-affinity to synthetic A2RE oligonucleotides, which presumably have little secondary structure, interaction with hnRNP A2 may not require extensive secondary structure.…”
Section: A2res In ␣Camkii Ng and Arc Rnas Bind To Hnrnp A2 In Vitromentioning
confidence: 96%
See 2 more Smart Citations
“…The A2RE-dependent targeting of mRNAs is also involved in the dendritic delivery of Arc, CaMKIIa, and Neurogranin mRNAs, which appear to cluster in the same hnRNPA2-containing granules (Gao et al, 2008). Moreover, hnRNPA2 was also shown to be necessary for the delivery of the non-coding BC1 RNA and PKMz mRNA to distal dendritic domains (Muslimov et al, 2006(Muslimov et al, , 2011. (Cajigas et al, 2012;Lein et al, 2007;Poon et al, 2006;Zhong et al, 2006) was compared with the rat genes present in the Agilent Technologies Whole Rat Genome Microarray (https://earray.chem.agilent.com/ earray/catalogGeneLists.do?action¼displaylist#) using GOrilla.…”
Section: Cis-acting Elements and Mrna Transport Into Dendritesmentioning
confidence: 97%